(untitled) (Global Journal of Medical Research, 2025)
Primary Hypertension is a multifactorial condition and a significant public health concern due to its link with cardiovascular disease. Factors such as obesity, smoking, and genetics contribute to its development. This study examined demographic and biological parameters in hypertensive and normotensive individuals, revealing that ethnicity and family history strongly influence Hypertension risk, particularly among Black participants and those with affected relatives. Hypertensive patients showed higher BMI and waist circumference, with age also contributing to onset. Other parameters, including hip circumference and lipid profiles, were similar between groups.